An Affinity Reagent for the Recognition of Pyrophosphorylated Peptides1. (4th February 2015) - Conway, John H.; Fiedler, Dorothea
Abstract A resin‐bound dinuclear zinc(II) complex for the selective capture of pyrophosphopeptides is reported. The metal complex binds diphosphate esters over other anionic groups, such as monophosphate esters, sulfate esters, and carboxylic acids, with high specificity. Immobilization of the compound provided a reagent capable of binding and retaining nanomolar quantities of pyrophosphopeptide in the presence of cell lysate. The high affinity and specificity of the reagent makes it an attractive tool for the study of in vivo pyrophosphorylation.